Tingkat Keamanan Dan Kepuasan Pelanggan Kereta Api Di Stasiun Kereta Api Muara Enim - Jannah, Miftahul; Afriyani, Asia; Septiana, Rika; Emiyati, Emiyati (Lex Librum : Jurnal Ilmu Hukum, 2026)
This study is entitled “Security Level and Customer Satisfaction of Railway Services at Muara Enim Train Station.” The research employs a qualitative descriptive method with data collection techniques including questionnaires, interviews, and documentation. Additionally, observational data were used by comparing existing conditions with standards and theories regarding security assurance, customer satisfaction, and the Good Public Space Index as an analytical tool. The analysis and observations indicate that 73% of respondents strongly agree that security is a highly important factor for train passengers. A sense of safety enhances passengers’ trust and willingness to use rail transportation. Regarding the security inspection at Muara Enim Station, 30% of respondents reported being very satisfied. Concerning security equipment at the station, 30% of respondents strongly agreed, 33% strongly agreed, and 37% agreed that the equipment is acceptable. For surveys on the importance of station security screening facilities (screening gates), 33% of respondents strongly agreed, 33% agreed, and 27% also agreed that these facilities are important. The highest level of satisfaction was reported for station staff services and accessibility between rooms at Muara Enim Train Station.